Telaah Deskriptif Motivasi Berprestasi Mahasiswa Penerima Beasiswa Kartu Indonesia Pintar Kuliah (KIP-K) - Marita, Tria; Prayogi, Arditya (Ruang Publikasi Ilmiah, 2024)
Motivation is the basic urge that moves someone to behave. Motivation will help direct individuals to achieve what they want. Providing motivation is very important for someone who is pursuing their education. One thing that can trigger motivation is the provision of scholarships, one of which is the Smart Indonesia-College Card (KIP-K) scholarship. This article aims to provide an overview of student achievement motivation and what are the driving and inhibiting factors for achievement motivation of PAI study program students receiving KIP-K scholarships Class of 2020, Faculty of Tarbiyah and Teacher Training, UIN K.H. Abdurrahman Wahid Pekalongan. This article was written using a descriptive qualitative approach using interview and documentation methods, and analyzed using a qualitative analysis model in the form of data reduction, data presentation and drawing conclusions. From the results of the study, it was found that the achievement motivation of PAI study program students who received KIP-K scholarships at UIN K.H Abdurrahman Wahid Pekalongan was shown in the form of responsibility, courage to take risks, creative and innovative, good at managing time, and hard work. Apart from that, the factors driving motivation are high enthusiasm, encouragement from the family, and demands from the KIP Kuliah program. Meanwhile, the factors inhibiting student achievement motivation are difficulty dividing time, laziness, social environment and family economy.